Efektivitas Pelaksanaan Bimbingan Perkawinan dalam Rangka Meminimalisasi Konflik Rumah Tangga Pasangan Muda di Kantor KUA Kecamatan Sukarami Palembang - RS, Syafarudin Bina; Novaria, Eva; Saswita, Saswita (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
Marriage guidance (bimwin) is a service provided by the Ministry of Religious Affairs through the Office of Religious Affairs (KUA), aimed at equipping prospective brides and grooms with the knowledge and skills to build a harmonious family. This study aims to analyze the effectiveness of marriage guidance in minimizing domestic conflict among young couples at the KUA in Sukarami District, Palembang City. This qualitative case study research involved in-depth interviews with religious instructors, KUA staff, and young couples participating in the bimwin program, as well as analysis of KUA documents and divorce case data. The results indicate that bimwin at the Sukarami KUA is relatively effective in increasing prospective brides and grooms' knowledge regarding rights and obligations, communication, and conflict management, although challenges remain, including limited counselors, facilities, and participant awareness. This study recommends improving the quality of materials, interactive methods, and post-marital monitoring.